Dry Eye Disease Among Mongolian and Han Older Adults in Grasslands of Northern China: Prevalence, Associated Factors, and Vision-Related Quality of Life - Wu, Jianhua; Wu, Xiaomei; Zhang, Han; Zhang, Xiaoguang; Zhang, Jie; Liu, Yanqiu; Liu, Jun; Lu, Lu; Zhang, Song; Zhang, Guisen; Liu, Lei (Frontiers in Medicine, 2021)
Purpose: Dry eye disease (DED) is projected to have increasing public health burden in China with the aging population. No published studies on the epidemiology of DED have been found in grasslands. We estimated DED prevalence among older adults living in grasslands of northern China and investigated its associated factors and impact on vision-related quality of life (VR-QoL). Methods: A multistage cluster random sampling technique was used to select Mongolian and Han participants aged over 40 from November 2020 to May 2021 in this area. An assessment of DED was performed with Ocular Surface Disease Index (OSDI) questionnaire, Schirmer's I test (ST), and Tear film break up time (TBUT). All the participants completed the Chinese version of National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) assessing VR-QoL. Results: Of the 1,400 enumerated residents, 1,287 were examined. The overall age and gender standardized prevalence of DED was 34.5%, of which, 32.6% of Mongolian and 35.4% of Han had DED. In a multivariate model, statistically significant associations were found with advancing age [odds ratio (OR) 1.03, 95% confidence interval (CI) 1.02–1.04], female gender (OR 1.32, 95% CI 1.04–1.68), smoking (OR 0.7, 95% CI 0.5–0.98), anti-fatigue eye-drop use (OR 0.56, 95% CI 0.41–0.77), milk product intake (OR 0.55, 95% CI 0.39–0.77), number of household members (OR 0.8, 95% CI 0.72–0.88). DED was associated with lower scores on VR-QoL (β= −0.14, P < 0.01). Similar results were observed when analyses were stratified by ethnicity. Conclusions: The novelty-associated factors for DED in the grasslands area were anti-fatigue eye drop use, milk product intake, and number of household members. DED and its components were associated with VR-QoL. Further prospective studies are needed to confirm these findings.